“No Regrets” Purchasing in a pandemic: making the most of advance purchase agreements - Ian Thornton; Paul Wilson; Gian Gandhi (Globalization and Health, 2022)
Abstract “No regrets” buying – using Advance Purchase Agreements (APAs) – has characterized the response to recent pandemics such as Avian flu, Zika Virus, and now COVID-19. APAs are used to reduce demand uncertainty for product developers and manufacturers; to hedge against R&D and manufacturing risks; and to secure availability of products in the face of spiking demand. Evidence on the use of APAs to buy vaccines, medicines, diagnostics, and personal protective equipment during recent pandemics illustrates how these contracts can achieve their intended objectives for buyers. But, transferring risk from suppliers to buyers - as APAs do - can have consequences, including overbuying and overpaying. Furthermore, the widespread use of APAs by high-income countries has contributed to the striking inequities that have characterized the Swine flu and COVID-19 responses, delaying access to vaccines and other supplies for low- and middle-income countries (L&MICs). We identify seven ways to address some of the risks and disadvantages of APAs, including adoption of a global framework governing how countries enter into APAs and share any resulting supplies; voluntary pooling through joint or coordinated APAs; a concessional-capital-backed facility to allow international buyers and L&MICs to place options on products as an alternative to full purchase commitments; greater collection and sharing of market information to help buyers place smarter APAs; support for a resale market; building in mechanisms for donation from the outset; and transitioning away from APAs as markets mature. While a binding global framework could in theory prevent the competitive buying and hoarding that have characterized country/state responses to pandemics, it will be very challenging to put in place. The other solutions, while less sweeping, can nonetheless mitigate both the inequities associated with the current uncoordinated use of APAs and also some of the risks to individual buyers. Analysis of recent experiences can provide ...